Skrining Fitokimia Ekstrak Daun Mangrove Rhizophora mucronata dan Rhizophora apiculata yang Dikoleksi dari Kawasan Mangrove Desa Tuban, Bali - Akasia, Alanis Ismi; Nurweda Putra, I Dewa Nyoman; Giri Putra, I Nyoman (Journal of Marine Research and Technology; Vol 4 No 1 (2021): FEBRUARI 2021DO - 10.24843/JMRT.2021.v04.i01.p03, 2021)
The content of secondary metabolite compounds in marine plants, especially mangrove has a certain bioactivity. Therefore, this study was aims to determine the content of secondary metabolites in the mangrove leaf extract of Rhizophora apiculata and Rhizophora mucronata . This study was conducted on January-April 2020. Sampling locations were carried out in the Mangrove Conservation Area of Tuban Village, Bali. In this study, samples were collected in the form of old leaves. The samples were taken in three sites and in each sites, 500 gr of leaves were collected randomly for each species. Therefore, in total we have 1.5 kg of leaves for each species. Samples are then extracted and tested to determine the content of secondary metabolites. The results showed the content of secondary metabolites in the leaves of R. apiculata mangrove were phenols, alkaloids, flavonoids, tannins, saponins, steroids while R. mucronata contained phenols, flavonoids, tannins, saponins, terpenoids.